2018
DOI: 10.1007/s11419-018-0415-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evaluation of new constituents of “Spice”: synthetic cannabinoids based on indole, indazole, benzimidazole and carbazole scaffolds

Abstract: PurposeIn the present study we characterized a series of synthetic cannabinoids containing various heterocyclic scaffolds that had been identified as constituents of “Spice”, a preparation sold on the illicit drug market. All compounds were further investigated as potential ligands of the orphan receptors GPR18 and GPR55 that interact with some cannabinoids.MethodsThe compounds were studied in radioligand binding assays to determine their affinity for human cannabinoid CB1 and CB2 receptors expressed in CHO ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
144
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(159 citation statements)
references
References 46 publications
(57 reference statements)
15
144
0
Order By: Relevance
“…As might be expected from available pharmacological data for structurally similar compounds, 4F‐MDMB‐BINACA has been shown by Jawalosky (as referenced in a recent World Health Organization Critical Review) to bind to the CB 1 receptor (4F‐MDMB‐BINACA at CB 1 : Ki = 14.3 nM; (R)‐(+)‐WIN‐55,212–2: Ki = 172 nM; Δ 9 ‐THC: Ki =22.5 nM using HEK cells and [3H]CP‐55,940 (~1.3 nM) as a radioligand) and to have functional activity as assessed using an adenylate cyclase assay using a cyclic AMP ELISA kit (4F‐MDMB‐BINACA, EC 50 = 0.20 nM (E max = 67.7%); (−)CP‐55,940, EC 50 = 0.40 nM (E max = 95.6%); Δ 9 ‐THC, EC 50 = 14.2 nM (E max = 82.9%)). To the best of the author's knowledge there is currently no publicly available data on the pharmacology of MDMB‐4en‐PINACA; however, based on existing structural–activity relationships it is highly likely to be a potent CB 1 and CB 2 receptor agonist …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As might be expected from available pharmacological data for structurally similar compounds, 4F‐MDMB‐BINACA has been shown by Jawalosky (as referenced in a recent World Health Organization Critical Review) to bind to the CB 1 receptor (4F‐MDMB‐BINACA at CB 1 : Ki = 14.3 nM; (R)‐(+)‐WIN‐55,212–2: Ki = 172 nM; Δ 9 ‐THC: Ki =22.5 nM using HEK cells and [3H]CP‐55,940 (~1.3 nM) as a radioligand) and to have functional activity as assessed using an adenylate cyclase assay using a cyclic AMP ELISA kit (4F‐MDMB‐BINACA, EC 50 = 0.20 nM (E max = 67.7%); (−)CP‐55,940, EC 50 = 0.40 nM (E max = 95.6%); Δ 9 ‐THC, EC 50 = 14.2 nM (E max = 82.9%)). To the best of the author's knowledge there is currently no publicly available data on the pharmacology of MDMB‐4en‐PINACA; however, based on existing structural–activity relationships it is highly likely to be a potent CB 1 and CB 2 receptor agonist …”
Section: Resultsmentioning
confidence: 99%
“…This, as well as the enactment of other national and international legislative controls, has led to a proliferation of new SCRA compounds, with 260 SCRAs being reported to the United Nations Office for Drugs and Crime (UNODC) by December 2018 and over 180 reported to the EU Early Warning System. The rate of the emergence of new compounds may be slowing, but there has been a general trend of increasing potency as the understanding of SCRA structure–activity relationships has improved …”
Section: Introductionmentioning
confidence: 99%
“…Among these tissue samples, the highest levels of unchanged mepirapim were found in the liver (6300 ng/g) and kidney (5410 ng/g), where drugs are usually metabolized and excreted into urine. It is unknown whether the vendors recommended the users to take high doses of mepirapim to gain sufficient drug effects; actually the affinities of mepirapim for both CB 1 and CB 2 receptors were low [6]. The most important problem for mepirapim is the toxicity of the compound; toxicity, pharmacokinetics and metabolism of this compound are all unknown and remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…MDMB‐CHMINACA was originally presented in a patent produced by Pfizer in 2009 (Example 129 in patent) to study the effects of compounds exhibiting CB 1 binding activity . Multiple studies to determine the CB 1 binding affinity (K i ) and receptor activation were previously conducted by researchers . Binding affinity was assessed through competitive binding assays with [ 3 H]CP 55,940, a cyclohexylphenol class synthetic cannabinoid; receptor activation was tested via a fluorometric imaging plate reader (FLIPR) assay .…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of MDMB‐CHMINACA at which the activation response was 50% of the response of the normalization compound (EC 50 ), was determined through this assay . A K i value of 0.0944 nM (at CB 1 ) was reported by Buchler et al Schoeder et al reported K i values of 0.135 nM (at CB 1 ), and 0.222 nM (at CB 2 ), demonstrating high affinity for both receptors. THC was also evaluated in the Schoeder et al study, and MDMB‐CHMINACA bound to CB 1 with approximately 30 times greater affinity (THC K i : 3.87 nM at CB 1 ).…”
Section: Introductionmentioning
confidence: 99%